Design and control of DFIG with SMES storage under symmetrical grid fault - Tariq Riouch; Cristian Nichita (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This paper presents a novel design and robust control for wind conversion systems using DFIG. The system is designed to reduce the problems related to the sudden variation of the wind speed and to improve the sensitivity of the DFIG to grid faults to avoid disconnection of the wind system from the electrical grid. To enhance the DFIG behavior, power fluctuation and to protect power devices under symmetrical faults, a specific superconducting magnetic energy storage (SMES) scheme and its control are proposed. To validate this study, the control structure and strategies were implemented in the MATLAB/Simulink environment. The results obtained by simulation were compared with those using traditional control strategies, they highlight an improvement in the functioning of wind conversion systems of this type, showing the rigor and effectiveness of the proposed strategy.